Correlation analysis between the prevalence of common respiratory pathogens and exposure to ambient air pollutants in Central China, 2014–2022 - Yaqi Zhu; Yaqi Zhu; Yuying Hou; Ting Xiang; Yingtao Wu; Xiaojian Cao; Xiaoxue Wu; Jinya Ding; Xionghui Zhou; Xiaohua Chen; Xiaohua Chen (Frontiers in Public Health)
BackgroundWhether ambient air pollutants affect the transmission of respiratory pathogens in central Wuhan is unknown. So, we conducted a series of statistical analyses to discover the correlation between the two.MethodsWe enrolled a total of 47,668 outpatient and hospitalized patients who underwent IgM antibody tests for nine types of respiratory pathogens, namely, Legionella pneumophila type 1 (LP1), Mycoplasma pneumoniae (MP), Q fever rickettsia (QFR), Chlamydia pneumoniae (CP), adenovirus (ADV), respiratory syncytial virus (RSV), influenza virus A (FluA), influenza virus B (FluB), and parainfluenza virus (PIVs) between January 2014 and December 2022. Monthly measurements were taken for specific air pollutants, including fine particulate matter 2.5 (PM2.5), inhalable particulate matter 10 (PM10), ozone (O3), nitrogen dioxide (NO2), sulfur dioxide (SO2), and carbon monoxide (CO) at the same periods. The association between different respiratory pathogen infections and major air pollutants was primarily analyzed using Spearman’s correlation analysis.ConclusionMP, LP1, and FluB are correlated with respiratory infections and have been identified as potential causative agents. Elevated levels of O3 were found to augment the incidence of MP infection. We first discovered the positive correlation between SO2 and ADV infection and between CO and LP1 infection. The presence of air pollutants in Wuhan showed a significant correlation with respiratory pathogens, and elevated levels of air pollution facilitated their transmission to individuals.